BIRACIAL IDENTITY IN I AM NOT YOUR PERFECT MEXICAN DAUGHTER BY ERIKA L SANCHEZ - Junia, Rusti; Ningtyas, Tutik Ratna (Elite : English and Literature Journal, 2025)
This research explains the biracial identity experiences by individuals. By analyzing “I am not Your Perfect Mexican Doughter” by Erika L Sanchez novel, the study aims to explore the biracial identity issue and how to deal with it so that it can be related to the real-life issues related to racial identity. Furthermore, this study reveals how the response given by the main character to negotiate the identity. This research uses a descriptive qualitative method because it enables the writer to describe the result holistically. Moreover, the data were collected to analyze the study in detail within the novel’s narrative. After gathering the data, they were analyzed using Stella Ting-Toomey and Tenzin Dorjee identity theory to demonstrate that the novel’s narrative relates to biracial identity experiences. The results of the study show a connection between biracial identity experiences and the response of the main character. Moreover, the findings show that the biracial experiences and struggles of identity in this novel are explained as having the potential of affect individual process of negotiating identity, both personally and socially.